Students’ Perceptions of Using Google Translate Platform As a Translation Medium in English Learning - Amrin Hi. Saban; Nurlaily Sofyan; Lili Nur Indah Sari Halek (Universitas Sulawesi Barat, 2026)
While Google Translate has become a ubiquitous tool in language classrooms, its pedagogical impact and how students critically engage with its limitations remain underexplored. This study aims to investigate students’ perceptions of the use of the Google Translate platform as a translation medium in English learning. In this study, the researchers applied a mixed-methods approach presented descriptively. The research instruments were questionnaires and an interview guide, designed to collect data. It employed a structured interview and then analyzed students’ perceptions through a questionnaire by applying a Likert scale. The sample comprised 15 third-semester students of the English Department at Muhammadiyah University of North Maluku, Indonesia, consisting of five males and ten females. The results showed that there is a positive and negative effect on students’ perception. The positive impacts are the students consider the use of it is important and very helpful in translating English texts. The result of translation is good, and it is very effective, faster, easy, and more practical; besides, it also facilitates pronunciation practice. Despite these limitations, such as network factors and potential grammatical errors, it can be said that Google Translate is generally perceived as effective for use as a translation medium in English learning. This study contributes to the field by expanding the empirical data on technological integration in outer-island Indonesian pedagogical contexts, mapping a definitive threshold where operational utility intersects with academic dependency.